Gambaran Imunohistokimia Synaptophisin pada Neuron Otak Tikus Pasca Mengalami Cedera Otak Traumatik: Immunohistochemistry of Synaptophisin in Rat Brain Neurons After Traumatic Brain Injury - Rohadi Rohadi; Bambang Priyanto; Lale Maulin Prihatina; Decky Aditya Zulkarnaen; Januarman Januarman; Bayu Putra Wibowo; Muzzaki Hasnan Ali; Gibran Ihza Sukma (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
TBI is mechanically followed by pathomechanisms that cause damage to surrounding neurons, such as cell and tissue necrosis, inflammation, cerebral edema, breakdown of the blood-brain barrier, and hyperthermia. The more severe the brain injury, the greater the impact on the inflammatory response. Therefore, this study aims to determine the histopathological description of edema in rat brain cells after TBI and to analyze the relationship between differences in trauma burden and histopathological features of brain cell inflammation, hematoma, and edema in mice after traumatic brain injury. This study uses an experimental observational-analytical research design. Sprague-Dawley mice were used as research subjects and divided into four cluster groups (and one control group) with varying trauma-loading interventions. The trauma loads given were 20 grams, 40 grams, 60 grams, and 80 grams. Following the trauma load application, the mice's brains were biopsied one hour after the intervention to observe histopathological features of inflammatory markers (synaptophysin) and brain cell edema. The data were then analyzed using the SPSS program. Twenty mice were included in this study. The results of the study showed that there was a mean load of 50 grams, and there is a mean synaptophysin percentage of 23.5%. There was a significant relationship between differences in trauma load and the percentage of post-TBI rat brain cell edema (p <0.001). There is a perfect and strong correlation between differences in trauma load and the percentage of synaptophysin (p=0.926). It was discovered that as the trauma load increased, there was a growing percentage of edema and inflammation in the histopathological features of the mice’s brains. There was a significant difference between the severity of trauma and the percentage of brain cell inflammation and edema one hour after brain injury in mice. The more severe the level of trauma given, the higher the percentage of inflammation and edema that occurs in rat brain cells. The result is especially notable since the inflammation and edema is found one hour within injury.